The awards of Spyridon Louis - Ставрос Цониас; Афанасиос Анастасиу (National University of Physical Education and Sport of Ukraine, 2017)
The article contains material on Spyridon Louis, the winner of the first Olympic Marathon in 1896. Many gifts given to him are described, in particular, the Silver Cup, which has become a family heirloom, and the silver medal kept at the Museum of the Marathon city (Greece). An original gift to Louis was a march composed by the conductor Kesaris.